IMPROVING STUDENTS' WRITING SKILL BY USING NOTE-TAKING PAIRS ON HORTATORY TEXT (A CLASSROOM ACTION RESEARCH IN SMA N 1GEMOLONG IN 2009/2010 ACADEMIC YEAR) - NINGRUM, IKA RIMA SHOLIKA (2011)
This research paper aims at describing the implementation of teaching writing using note-taking pairs on hortatory exposition text at the 11th year of SMA N 1Gemolong in 2009/2010 academic year, and the effectiveness of teaching writing by using note-taking pairs on hortatory text viewed from the students' perspective. The writer conducts classroom action research (CAR). The data are taken from event, informant, and document. The technique of collecting data are observation, test, and interview with the teacher and the students. The result s of the study show that first, the note-taking pairs is effective to improve the students' writing skill. It is proved that the students get selfconfidence, and the students get better grammar, mechanical consideration (spelling and punctuation), and vocabulary. Second, the note-taking pairs makes the students' writing skill improve in hortatory exposition text at the 11th year of SMA N 1 Gemolong in 2009/2010 academic year.